The Integrated Effects of Fertilizer on Sweet Potato (Ipomea Batatas, Lam.) in Andosol and Nitisol Soils - Tang, Erasmus Nchuaji; Ngome, Francis Ajebesone (International Journal of Sustainable Agricultural Research, 2022)
Sweet potato is a food and nutrition security crop in sub-Saharan Africa with low yields resulting from soil infertility. We examined the effects of nine fertilizer regimes on the growth performance of orange-fleshed (OFSP) and white-fleshed (WFSP) sweet potato varieties in two agro-ecological zones characterized by Andosol and Nitisol soils. The treatments were: NPK20-10-10, NPK6-15-28, rice husk biochar (RHB), fast compost (FC), Tithonia diversifolia leaf powder, poultry litter (PL), RHB/NPK20-10-10, FC/NPK20-10-10 and PL/NPK20-10-10. These were compared to a control of no fertilizer. The Andosol and Nitisol soils were acidic with significant differences (p < 0.05) in total nitrogen, organic carbon, C/N ratio, phosphorus, potassium, calcium and magnesium. Fertilizer effects were dominant on the adventitious root, total and marketable yields, moderately affecting main stem length and harvest index (HI) with weak effects on branch number, petiole length and leaf area index (LAI). Soil type and sweet potato variety strongly affected main stem length and HI. Variety × fertilizer strongly influenced adventitious root formation, while soil × variety × fertilizer affected total and marketable yields. LAI, primary branch number, dry biomass, total and marketable yields were best for the OFSP in the Andosol, while main stem length, petiole length, adventitious roots and HI were best for the WFSP in the Nitisol. Results of the study showed that FC, PL/NPK20-10-10 and RHB/NPK20-10-10 were the most promising soil fertility amendments to boost sweet potato productivity in the Nitisols and Andosols.